PENGARUH PEMBERIAN EKSTRAK KELOPAK BUNGAROSELLA (Hibiscus sabdariffa L.) TERHADAP HISTOPATOLOGI SPERMATOGENESIS TIKUS PUTIHJANTAN (Rattus novergicus) GALUR WISTAR DENGAN PAPARAN ASAP ROKOK - Pisi Nopita Wigati (2020)
Indonesia is ranked third in cigarette consumption in the world. Cigarette smoke causes an increase in free radicals that can damage cells, one of which is spermatogenesis cells. Roselle petals are reported to contain flavonoids as antioxidants that can reduce free radicals. This study aims to compare the histopathological picture of spermatogenesis of male white rats (Rattus novergicus) Wistar strain given and not given rosella flower petal extract (Hibiscus sabdariffa L.), determine the effect of rosella flower extract (Hibiscus sabdariffa L.) on the histopathological picture of spermatogenesis L. male white rats (Rattus novergicus) Wistar strain with exposure to cigarette smoke and know the optimal dose of rosella flower petals extract (Hibiscus sabdariffa L.) against histopathological features of spermatogenesis of male white rats (Rattus norvegicus) Wistar strain with exposure to cigarette smoke. into four groups, each consisting of 7 individuals. The negative control group was given standard feed 551 and aquadest. The positive control group was given a standard feed of 551, aquadest and exposed to 2 cigarettes per day. Treatment group I was exposed to 2 cigarettes of cigarette smoked per day and rosella calyx extract dose of 270mg / kgBB. Treatment group II was exposed to 2 cigarettes per day of cigarette smoke and rosella calyx extract dose of 540mg / kgBB. The study was conducted for 52 days. At the end of the study, a testicular dissection was performed to see histopathological features of rat spermatogenesis. The results of the study with the One Way Annova test and the Post Hoc Tamhane test obtained the average spermatogenesis cells in 4 treatment groups with the lowest number in the positive control group and the best in the negative control group. Rosella extract dose of 270mg / kgBB and 540mg / kgBB was able to increase spermatogenesis cells, but there was no significant difference in value (p> 0.05) between the treatment groups.